Virtual Selves, Virtual Communities: Self-Narration and Social Relations in Multi-User Virtual Environments. (3rd May 2016) - Butler, Stephanie
ABSTRACT: Using case studies, the author analyzes how people with myalgic encephalomyelitis|chronic fatigue syndrome construct their subjectivities in the multi-user virtual environment Second Life. The findings of the study reveal people's anxieties about identity and belonging, especially where interlocking disadvantages such as economic class, gender, mental health, disability, and chronic illness influence who is accepted as a member of the support groups held in-world.